A Comprehensive Literary Review on the Posthumanism Reflected In Philosophy and Literature (International Journal of Food and Nutritional Sciences, 2022)
Posthumanism is an opposite philosophical conception to humanism. It is an umbrella termthat covers different philosophies like Antihumanism, Cultural Posthumanism, New materialism,Transhumanism and Artificial Intelligence (AI) Takeover.